Spiritualitas Ekaristi Henri Nouwen dalam Kehidupan Keluarga Katolik Pedesaan - Kristina Jela; Yanto Sandy Tjang; Felisitas Yuswanto (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2026)
This study aims to examine the lived experience of the Eucharist as an experience of love in the lives of Catholic families at St. Michael Buluq Sen Station, Good Shepherd Parish of Ritan Baru, Archdiocese of Samarinda, through the lens of Henri Nouwen’s spirituality. It employs a descriptive qualitative approach, with data gathered through observation, semi-structured interviews with eight active Catholic families, and a review of relevant literature. Data were analyzed through systematic stages of reduction, display, and conclusion drawing, supported by source and method triangulation. The findings show that the experience of the Eucharist is expressed in four interrelated dimensions of Nouwen’s spirituality: being chosen, blessed, broken, and shared. “Being chosen” appears in the family’s awareness of belonging to a community loved by God; “being blessed” is reflected in gratitude for life; “being broken” is revealed in the willingness to embrace suffering and sacrifice; and “being shared” is embodied in active participation in Church ministry and social engagement. This study affirms the Eucharist as a transformative source shaping family relationships and social life, enriching theology and supporting formation in rural families.